The polycentricity of urban population will lead to improvements in urban heat island effect: Evidence from the Yangtze river delta in China - Cheng Wang; Jingyuan Chen; Qinpei Wang; Dan Li; Meng Zhu; Zhiqiang Gan; Menglin Qin; Yunbin Zhang (Sustainable Futures)
Currently, major cities globally are universally and actively implementing strategies for the polycentric development of urban spatial structures. However, the impacts of this strategy on the ecological environment and residents' lives require further assessment. The urban spatial structure is believed to influence the urban heat island effect, but the specific mechanisms of this influence remain unclear. Exploring this topic can provide guidance for the development of ecological and residential environments. This paper primarily takes the rapidly developing Yangtze River Delta region in China as an example. It quantifies the degree of polycentricity and the heat island effect using population distribution data and land surface temperature data and finally analyzes the impact and mechanisms of polycentric development on the urban heat island effect using spatial econometric models. The results indicate that: (1) Between 2006 and 2020, the population distribution in the Yangtze River Delta region urban cluster exhibited a continuous trend toward polycentricity. The dispersion of population exhibited a slight increase but a relatively minor change overall. (2) Urban polycentricity significantly reduces the urban heat island effect. For every 1 % increase in urban polycentricity, the urban heat island in the city decreases by 0.697 %. Additionally, an increase in urban polycentricity alleviates the urban heat island effect in the surrounding areas, with a 1 % rise in urban polycentricity resulting in a 16.569 % reduction in urban heat island levels in the adjacent regions. (3) An increase in the degree of polycentricity will concentrate the urban population, increases the areas of impervious urban surfaces, and ultimately alleviate the urban heat island effect. At the same time, the growth of urban population and economic progress will further contribute to mitigating the urban heat island effect linked to polycentric urban development.